AN ASSESSMENT OF THE PATHOGENICITY OF Edwardsiella tarda AND TREATMENT OF EXPERIMENTAL EDWARDSIELLOSIS IN CULTURED Clarias gariepinus (CUVIER 1822) - OLADOSU, G.A; OLUFEMI, B.E.; IGHARA, O. (Nigerian Journal of Fisheries, 2016)
The pathogenicity of Edwardsiella tarda isolated from pond water, and chemotherapeutic control of experimental edwardsiellosis in cultured Clarias gariepinus were investigated. The E. tarda isolate was identified based on colony and cellular morphology, as well as biochemical characteristics. A total of 120 fish were randomly assigned to four groups (A, B, C and D) of 30 fish, each comprising of 15 fish replicated once. Fish in groups A, B and C were infected intra-peritoneally with 1.02x106 cfu of E tarda, while group D was not infected. Following observation of clinical signs, group A was treated with ciprofloxacin by 1hour immersion at 25mg/litre of water and group B orally at 100mg/kg body weight of fish for five days. Fish in group (C) were not treated with ciprofloxacin. Fish were observed for mortality daily, and cumulative mortality was compared between groups using ANOVA and Duncan Multiple Range Test. Cumulative mortality of 56.66% observed in group C was significantly higher (p < 0.05) than in groups A and B treated via oral (3.33%) and immersion (3.33%) route respectively. Infected fish were effectively treated by both routes of ciprofloxacin application, but the oral route is considered less stressful for the sick fish.